Cycling injuries? Prevention and treatment - Hutson, W. (2009)
The human body makes contact with the bike at three points; hands (handlebars), pelvis (saddle) and the feet (pedals). If these three points of contact are disregarded and set up incorrectly then almost certainly overuse and traumatic injuries will occur. One can try to adjust the bike to the person but one cannot adjust the person to the bike without a great deal of difficulty.